2017
DOI: 10.1073/pnas.1614447114
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging reveals that pregabalin inhibits cortical spreading depression and propagation to subcortical brain structures

Abstract: Migraine is characterized by severe headaches that can be preceded by an aura likely caused by cortical spreading depression (SD). The antiepileptic pregabalin (Lyrica) shows clinical promise for migraine therapy, although its efficacy and mechanism of action are unclear. As detected by diffusion-weighted MRI (DW-MRI) in wildtype (WT) mice, the acute systemic administration of pregabalin increased the threshold for SD initiation in vivo. In familial hemiplegic migraine type 1 mutant mice expressing human mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 47 publications
3
62
1
Order By: Relevance
“…Had the drug worked extracellularly to block allodynia in vivo, it would have been washed away by the time spinal cord slices were studied and no persistent effect of the drug would be seen. This supposition is supported by detailed quantitative arguments outlined in our paper (Alles et al, 2017). These observations are congruent with those of Lana et al (2016), who showed that GBP displacement of thrombospondin 4 binding (see below) is effected at an intracellular site on a2d-1.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…Had the drug worked extracellularly to block allodynia in vivo, it would have been washed away by the time spinal cord slices were studied and no persistent effect of the drug would be seen. This supposition is supported by detailed quantitative arguments outlined in our paper (Alles et al, 2017). These observations are congruent with those of Lana et al (2016), who showed that GBP displacement of thrombospondin 4 binding (see below) is effected at an intracellular site on a2d-1.…”
supporting
confidence: 91%
“…This was observed as an increase in the amplitude of Ca 2+ responses evoked by 35 mM K + (Lu et al, 2007;Alles et al, 2017). In addition, activated microglia-conditioned medium increased overall organotypic slice excitability, and preincubation of slices with a TrkBd5 (recombinant receptor, which sequesters BDNF) inhibited this effect (Lu et al, 2009).…”
Section: +mentioning
confidence: 98%
See 3 more Smart Citations